THE EFFECT OF DIGITAL MARKETING AND PRODUCT QUALITY ON CONSUMER PURCHASE INTEREST IN THE MARKETPLACE SHOPEE DURING PANDEMIC - Shelli Safitri; Syahmardi Yacob; Yenni Yuniarti (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
The Covid-19 pandemic has stopped human mobility, and this has affected the economic sector in almost all countries. One strategy that can be done to survive during the pandemic is to trade online by promoting digitally in the marketplace using digital marketing. This study aims to analyze the effect of Digital Marketing and Product Quality on consumers' buying interest in the SHOPEE Marketplace during the pandemic simultaneously and partially. And, it aims to find out which factors are more dominant in influencing consumer buying interest in the SHOPEE marketplace during the pandemic. The research method used is descriptive quantitative with a sample of 100 respondents using purposive sampling technique. Data analysis used multiple linear regression. The results showed that Digital Marketing and Product Quality had a positive and significant effect on consumers' buying interest in the SHOPEE Marketplace during the pandemic simultaneously and partially. Product quality variables are more dominant in influencing consumer buying interest in the SHOPEE Marketplace during the pandemic